1983
DOI: 10.1016/0022-5088(83)90232-1
|View full text |Cite
|
Sign up to set email alerts
|

The texture of diffusion-grown HfAl3 layers

Abstract: SummaryHfA1, layers were grown on hafnium and aluminium substrates. A [OOl] fan texture was observed in HfAl, grown by solid state diffusion on textureless hafnium substrates. If layers were grown on a hafnium substrate with a pronounced single-component sheet texture, the texture in the HfAl, layer was not rotationally symmetric around the direction of diffusion, but a related sheet texture developed. An orientation relation is proposed. Layers grown from the vapour phase on aluminium substrates show an (84… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 5 publications
2
8
0
Order By: Relevance
“…These Si atoms react with the substrate Nb atoms at the growth front, i.e., the NbSi 2 layer-substrate interface, to form further NbSi 2 phase. There is experimental evidence that Si diffusion is much faster than metal diffusion in transition metal disilicides such as NbSi 2 , MoSi 2 , WSi 2 , VSi 2 and TaSi 2 [30,31]. In fact, Salamon and Mehrer [32] have shown that the tracer diffusion of 71 Ge in MoSi 2 is orders of magnitude faster than 99 Mo.…”
Section: Discussionmentioning
confidence: 98%
“…These Si atoms react with the substrate Nb atoms at the growth front, i.e., the NbSi 2 layer-substrate interface, to form further NbSi 2 phase. There is experimental evidence that Si diffusion is much faster than metal diffusion in transition metal disilicides such as NbSi 2 , MoSi 2 , WSi 2 , VSi 2 and TaSi 2 [30,31]. In fact, Salamon and Mehrer [32] have shown that the tracer diffusion of 71 Ge in MoSi 2 is orders of magnitude faster than 99 Mo.…”
Section: Discussionmentioning
confidence: 98%
“…Here we discuss the impact of extra freedom on the 1d-APD in detail [19][20][21][22][23]47] to assess the stability of D0 22 -TiAl 3 at elevated temperature, using n = 8 series as an example. Assuming that there is one 1d-APD in this configuration, then this structure has (a) an formation energy of about −0.070 eV/cell or −0.009 eV/TiAl 3 with respective to that of D0 22 , (b) freedom of configurations, w = 8 due to the fact that such 1d-APD may occur for each TiAl 3 unit in the cell.…”
Section: Discussion: 1d-apd In D0 22 -Tial 3 Chain and Configurationmentioning
confidence: 99%
“…Tang and co-workers performed first-principles calculations for some one-dimensional long period structures (1D-LPSs) based on the cubic L1 2 -TiAl 3 [45,46]. In the present manuscript, we have analysed systematically the existing TiAl 3 phases and predicted various stackings by application of the one-dimensional antiphase domain (1d-APD) model [19][20][21][22][23]47] based on the D0 22 structure using ab initio density functional theory (DFT). We also performed DFT calculations with hybrid-functional correction for the three known TiAl 3 (L1 2 , D0 22 and D0 23 ) phases.…”
Section: Introductionmentioning
confidence: 99%
“…Because of its distinct crystal structure, composition, lattice parameter and so misfit, D0 22 Ni 3 V may exhibit a different morphology to L1 2 Ni 3 Al as well as different coarsening kinetics and strengthening effects [12,13,14]. D0 22 Ni 3 V has lattice parameters of a = 3.543 Å, c = 7.221 Å [15], compared to those for metastable D0 22 Ni 3 Nb of a = 3.62 Å, 25 c = 7.41 Å [7].…”
mentioning
confidence: 99%
“…The Ni 3 V phase offers some advantages over Ni 3 Nb as it is thermodynamically stable and 30 has a different lattice misfit, δ. Given δ = 2(a γ −a γ )/(γ +a γ ) and a γ = 3.51 Å, δa γ -a N i3V ∼ 0.9%, and δa γ -c N i3V ∼ 2.8%, in contrast to δa γ -a N i3N b ∼ 3.1%, and δa γ -c N i3N b ∼ 5.4%, taking the lattice parameters given earlier for Ni 3 V [15] and Ni 3 Nb [7]. Further, it is possible to have controlled precipitation of L1 2 Ni 3 Al with optimised volume fraction and size before producing D0 22 Ni 3 V 35 at a lower temperature.…”
mentioning
confidence: 99%